Risk Factors Associated With Diabetic Retinopathy: A Cross-Sectional Study Within Palestinian Patients in Northern West Bank - Amer, Johnny; Suboh, Raghad; Abualrob, Manar; Shaheen, Amira; Abu Shanab, Abdul Raheem (Frontiers in Clinical Diabetes and Healthcare, 2021)
Risk factors associated with diabetes mellitus (DM) have been widely researched worldwide, but the determinants of these factors among diabetic retinopathy (DR) in Palestine are currently unclear. We aimed to assess the prevalence of DR among DM in Northern West Bank and identify factors associated with DR natural history. Patients with Type 2 diabetes (T2D) (n = 300, age > 18 years) from a main diabetic center covering all northern provinces of Palestine were enrolled to this cross-sectional research. Demographic information including age, sex, and duration of T2D was obtained. Moreover, HbA1C, BMI, hypertension (HTN), controlled T2D, current smoking, and total cholesterol level were assessed. Potential correlations between these factors and DR diagnosed by ophthalmologist were evaluated using different tests on SPSS version 22. Prevalence of DR among our population was 30%; 47.8% of these patients showed mild non-proliferative DR (NPDR), 23.3% moderate NPDR, 16.7% severe NPDR, and 12.2% proliferative DR (PDR). Univariate logistic regression analysis showed age (p = 0.007), HTN (p = 0.022), uncontrolled T2D (p = 0.025), and duration of T2D (<0.001) were mostly associated with DR while multivariate logistic regression showed duration of T2D as the major and solely risk factor for prevalence of DR (p < 0.0001) and were positively correlated with severities of NPDR and being a strong predictor in the PDR (p = 0.001). We identified several important risk factors that affect DR, which could assist to develop effective strategies for metabolic disease prevention among populations in Palestine. Furthermore, our data suggest a necessity to control sugar serum levels and HTN.